‘KNOW YOUR BODY, PROTECT YOURSELF’ PROGRAM: A PREVENTIVE APPROACH TO PREMARITAL SEXUAL BEHAVIOR AMONG ADOLESCENT: ‘KNOW YOUR BODY, PROTECT YOURSELF’ PROGRAM: CLINIC-BASED GROUP EDUCATION IN PREVENTING PREMARITAL SEX AMONG TEENS AT UNIB MEDICAL CENTER PRIMARY CLINIC - Innas Tiara Ardhiani; Syeri Febriyanti; Rini Mustikasari Kurnia Pratama (Universitas Airlangga, 2026)
Adolescent reproductive health is a crucial issue that needs serious attention, considering the increasing cases of premarital sexual behavior and its negative impact on the health and future of the younger generation. According to BPS Bengkulu Province Data (2023), the current issue being faced is the high incidence of premarital sex among teenagers, with data showing that the birth rate for teenagers aged 15–19 years reaches 31 per 1,000 females, above the national average. The committee was motivated to carry out this community service activity for teenagers due to concerns about the prevalence of promiscuous behavior among adolescents, the lack of understanding of reproductive health, and the still low active involvement of educational institutions in sexual health prevention programs. The activity was conducted at the UNIB Medical Center Pratama Clinic with the provision of materials, question and answer sessions, a participatory educational approach based on peer groups, as well as pre-tests and post-tests. A total of 40 students participated, and the results showed a significant increase in knowledge and attitude changes. The challenge faced was the limited space at the UNIB clinic, but it was successfully overcome by moving the activities to the campus seminar room. The presence of this activity is expected to increase the participation of campus clinics in education on adolescent reproductive health and pre-marital sex.